anti-caste : on caste, women's oppression, communalism, and class struggle in South Asia from a Marxist perspective (2009)
[Dt.:] Diese Seite bietet Artikel zum Kastenwesen und anderen Formen von Diskriminierung. Die zwei Autoren, wovon eine selbst aus einer Dalit Familie stammt, betonen ihre marxistische Perspektive, jedoch auch dass sie keine politische Partei oder Organisation seien. Außer den Artikeln, die nach verschiedenen Themen- und Regionalgebieten gegliedert sind, bietet die Seite auch relevante Nachrichten. - [Engl.:] This website about the caste system and other forms of discrimination has the purpose to share the ideas and research of the authors on that topics. The authors, one of them herself of Dalit origin, underline their marxist perspectives but also that they aren't any kind of organization or political party. The site provides articles about different topics around the theme and news.